2002
DOI: 10.1076/jcen.24.3.370.984
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of Total Score Performance on the Rey–Osterrieth Complex Figure and a Modified Taylor Complex Figure

Abstract: One of the most commonly used neuropsychological measures of visuo-spatial abilities is the Rey-Osterrieth Complex Figure (ROCF) Test. Previous research has reliably shown that its companion figure, the Taylor Complex Figure, is not a comparable measure of visuo-spatial memory. The aims of the three studies presented here are to (a) introduce a modified version of the Taylor Figure (MTCF), and (b) examine the comparability of the ROCF and the MTCF using two different administration procedures. The first two st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…1): the Rey-Osterrieth Complex Figure Hubley, 1996). Comparability of the ROCF and the MTCF has been confirmed in several studies (Hubley & Jassal, 2006;Hubley & Tremblay, 2002), while the TCF was found to be easier than the ROCF (e.g., Tombaugh, Faulkner, & Hubley, 1992;Yamashita, 2006). We balanced the assignment of the three figure versions to the three experimental conditions and the order of presentation so that the effect of difficulty should not affect the interpretation of results.…”
Section: Assessment Of Visual Memorymentioning
confidence: 73%
“…1): the Rey-Osterrieth Complex Figure Hubley, 1996). Comparability of the ROCF and the MTCF has been confirmed in several studies (Hubley & Jassal, 2006;Hubley & Tremblay, 2002), while the TCF was found to be easier than the ROCF (e.g., Tombaugh, Faulkner, & Hubley, 1992;Yamashita, 2006). We balanced the assignment of the three figure versions to the three experimental conditions and the order of presentation so that the effect of difficulty should not affect the interpretation of results.…”
Section: Assessment Of Visual Memorymentioning
confidence: 73%
“…This may result in improved performance, particularly in older populations [65] . Impaired performance on the initial administration of this test may therefore be more indicative of poor attention and/or motivation than poor memory [64] .…”
Section: Discussionmentioning
confidence: 99%
“…The RCFT-R also differs from the other memory tests in our battery, at least during subjects' initial exposure, because it represents an incidental rather than intentional memory task. In subsequent administrations, the RCFT-R likely becomes an intentional memory task given subjects' prior experience [64] . This may result in improved performance, particularly in older populations [65] .…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive battery was administered at both baseline and follow-up covering the well-established domains of complex attention, processing speed, learning and memory, spatial processing, and executive functioning (Lezak et al, 2004 (Corwin and Bylsma, 1993;Hubley and Tremblay, 2002); Wechsler Abbreviated Scale of Intelligence (WASI) Block Design subtest (Wechsler, 1999) Composite categories were developed for each of the fi ve domains to reduce the number of dependent variables for correlations with cortical thickness. Individual z scores were created for each subject, neuropsychological variable, and time point based on the whole sample of adolescents and corresponding standard deviations (N = 54).…”
Section: Methodsmentioning
confidence: 99%